KRITIK HADIS NIKAH SIRI (DITINJAU DARI BERBAGAI ASPEK) - Fatihunnada Fatihunnada (TAHKIM, 2017)
Prophet prohibition against the practice of unofficial marriages contain vast dimensions. In terms of sociology, described the social order which assesses the existing norms as a benchmark in the behavior of individuals that must be maintained. Then in terms of the philosophy, describing, that marriage is not based on the views of pleasure and has been duly carried out with the intention of pure and contains goodness. Then in terms of economy illustrate that no matter how the benefits achieved in the nikah siri by some stakeholders, but causing no less great losses will be felt by the perpetrators nikah siri. Even in terms of psychology, describing the condition of mental collapse actors siri marriage and family nearby to socialize with the surrounding community. Data was collected using library research methods to the Prophet's hadith literature and case studies related, then scrutinized by analyzing existing data, both in terms of sanad and matn in detail and a comprehensive approach to sociology, philosophy, economics, psychology and others. Findings, is nikah siri in view of the Prophet contain several negative risks for some stakeholders, so that the necessary legal protection official in marriage to prevent it. This paper will strengthen the Bill of Law Petition article 143 Religious Courts Marital field that contains criminal prosecution against the perpetrators nikah siri and related parties. Keywords: tradition, unregistered marriages, criminal